2010
DOI: 10.1029/2009jd013143
|View full text |Cite
|
Sign up to set email alerts
|

Vertical distributions of lightning sources and flashes over Kennedy Space Center, Florida

Abstract: [1] Warm season vertical distributions of lightning sources and flash segments are presented using data from the lightning detection and ranging network at Kennedy Space Center, Fla. We emphasize the percentage of sources/flash segments at each level compared to the vertical total and present the distributions as a function of storm top above ground level (AGL). The vertical profiles of sources and flash segments are compared with each other and with those from previous studies. Results indicate that storms wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 49 publications
2
16
0
Order By: Relevance
“…This result illustrates the geometric basis for using the vertical histogram of VHF sources to weight NO x production, as was done by Hansen et al [2010].…”
Section: Fractal Length Estimatesmentioning
confidence: 99%
“…This result illustrates the geometric basis for using the vertical histogram of VHF sources to weight NO x production, as was done by Hansen et al [2010].…”
Section: Fractal Length Estimatesmentioning
confidence: 99%
“…Mecikalski and Carey () showed that peaks in the profiles of LMA VHF sources (i.e., where flashes propagate) occur at different altitudes and reflectivities than were found for flash initiation points only, and therefore, information on where flashes propagate relative to reflectivity and altitude is also important. Similarly, Boccippio et al () and Hansen et al () both showed that the locations where flashes initiate and propagate are different; Boccippio et al () specifically found the peak in the VHF sources (i.e., for the entire path of the flash) to be located at ~9.5 km, while Hansen et al () found this peak to be located between 8 and 10 km for multicellular storms that occurred over Florida. Therefore, if one wants to have a complete picture of the lightning distribution within a storm, one needs to analyze where lightning both initiates and propagates.…”
Section: Introductionmentioning
confidence: 98%
“…The locations of the major charge regions prior to triggering lightning are inferred from the preceding natural lightning activity. There have been a number of studies which used Lightning Detection and Ranging VHF data to study lightning in Florida [e.g., Rustan et al, ; Krehbiel et al, ; Williams et al, ; Boccippio et al, ; Ushio et al, ; Hansen et al, ], but this is the first study of thunderstorm charge structure in Florida using the more sensitive LMA. LMA data for the entire triggered flash, IS and all following electrical activity (leader/return stroke sequences and interstroke processes), will be included in the analysis.…”
Section: Introductionmentioning
confidence: 99%